Discordance between patient with cancer and caregiving partner self-reported financial toxicity. Issue 28 (1st October 2022) - Rivers, Zachary; Shankaran, Veena; Porter, Laura S; Langer, Shelby
Abstract : 182 Background: While financial toxicity (FT) is a well-documented problem facing cancer patients, few studies have simultaneously investigated the financial experiences of patients and their caregiving partners. Here, we report concordance and discordance in experiences of FT between cancer patients and their caregiving partners. Methods: Patients aged ≥18 with stage II-IV breast, lung, or colorectal cancer who had received treatment within the past two years and were married or in a committed, cohabitating relationship were enrolled along with their partners. Patient and caregiver responses to the FACIT-COST (lower scores indicating higher FT; score ≤ 26 meeting FT threshold) were calculated, and dyads were categorized as concordant or discordant in their experience of FT. Logistic regression models were used to explore patient and caregiver predictors of FT. Results: A total of 327 dyads (median patient age 53, 45% stage IV, 36% breast, 44% colorectal, 19% lung) were included in the analysis. Numeric COST scores were lower in patients (27, IQR: 19, 25) than in caregivers (30, IQR: 23, 37) and more patients than caregivers met the threshold for FT (45% vs. 34%, p = 0.002). Both members of the dyad had similar FT experiences in 74% of cases (26% and 48% reported FT and no FT respectively) while 26% diverged in their experience of FT (8% of partners reported FT while the patient did not; 18% of patients reported FT while the caregiver did not.) Higher patient age was associated with a reduced odds of patient-reported FT (OR for each year: 0.92, 95% CI 0.86-0.98) while higher odds of FT was seen with increased patient comorbidities (OR: 1.56, 95% CI: 1.26-1.96 for each comorbidity) and patient race (Black OR: 1.41 - > 10 compared to White). Similarly, caregiver comorbidity, caregiver race, and female sex increased the odds of caregiver-reported FT. In addition, the odds of caregiver-reported FT were higher with lower annual household income (60, 000-120, 000: OR: 0.26, 95% CI: 0.09-0.73, > 120, 000: OR 0.15, 95% CI 0.04-0.51 compared to less than 60, 000), and the presence of children in the home (OR: 4.15, 95% CI: 1.88-9.67). Conclusions: More than a quarter of patients and caregivers had discordant experiences of FT. Assessing both members of a patient-caregiver dyad for FT is therefore critical to understanding the household financial impact of cancer diagnosis and treatment.